(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The complex structure and large size of network databases make it difficult to effectively visualize them. This article highlights the importance of data cleaning methods in the process of depicting network data in 3D format. The article considers the stages of identifying incorrect, duplicate and unnecessary data, their correction and standardization. Using cleaned and accurate data, it is shown how to improve the quality of the visualization process and effectively analyze it through a graphical model of the network. This article presents new approaches to 3D visualization and data management from a scientific and practical perspective.